Cleaning the gold eaudiobook - Slaughter, Karin (Jack Reacher, 2019)
THE NEW SHORT STORY FROM KARIN SLAUGHTER AND LEE CHILD! Jack Reacher and Will Trent Twice the action. Twice the drama. Double the trouble. Will Trent is undercover at Fort Knox. His assignment: to investigate a twenty-two-year-old murder. His suspect's name: Jack Reacher. Jack Reacher is in Fort Knox on his own mission: to bring down a dangerous criminal ring operating at the heart of America's military. Except now Will Trent is on the scene. But there's a bigger conspiracy at play – one that neither the special agent nor the ex-military cop could have anticipated. And the only option is for Jack Reacher and Will Trent to team up and play nicely. If they can...